2020
DOI: 10.1016/j.jjcc.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Limited efficacy of a figure-of-eight suture for hemostasis after cryoballoon atrial fibrillation ablation with uninterrupted oral anticoagulants

Abstract: Introduction: There are limited data on the efficacy and safety of a figure-of-eight (FoE) suture technique after atrial fibrillation (AF) ablation with uninterrupted oral anticoagulants (OACs). This study evaluated the predictors of bleeding complications at the femoral puncture site after placing a FoE suture to achieve hemostasis after AF ablation with OACs. Methods: We enrolled 287 consecutive patients who underwent a 1st session of AF ablation using radiofrequency or cryoballoon ablation. Hemostasis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Since dabigatran can also prolong APTT in a dose-dependent manner [19] , the anticoagulant effect of dabigatran persisted up to the time of vascular puncture in the < 8 h group, which might have led to the increased incidence of major bleeding events. In fact, a recent report showed that the effect of the suture technique at vascular access sites on hemostasis after AF ablation with uninterrupted DOAC was small [20] .…”
Section: Anticoagulation Implications Of a Short Period Of Interrupti...mentioning
confidence: 99%
“…Since dabigatran can also prolong APTT in a dose-dependent manner [19] , the anticoagulant effect of dabigatran persisted up to the time of vascular puncture in the < 8 h group, which might have led to the increased incidence of major bleeding events. In fact, a recent report showed that the effect of the suture technique at vascular access sites on hemostasis after AF ablation with uninterrupted DOAC was small [20] .…”
Section: Anticoagulation Implications Of a Short Period Of Interrupti...mentioning
confidence: 99%